2009
DOI: 10.2466/pms.109.1.30-40
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Reynolds Intellectual Assessment Scales and the Wechsler Adult Intelligence Scale-Third Edition

Abstract: The purpose of this study was to compare scores on the Reynolds Intellectual Assessment Scales (RIAS) with scores on the Wechsler Adult Intelligence Scale-Third Edition (WAIS-III) in a group of college students diagnosed with a Learning Disability, Attention-Deficit Hyperactivity Disorder (ADHD), or a combination of the two. The RIAS Composite Index score was significantly higher than the WAIS-III Full Scale IQ, although scores on both tests were in the average range. Correlations between the two tests were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…However, the current findings do make intuitive sense from the standpoint that both the WISC-IV and the RIAS were normed on large nationally stratified samples, their indexes and IQs are standardized and age corrected, and their verbal (VIX/VCI) and nonverbal (NIX/PRI) indexes assess conceptually similar constructs. Furthermore, the nonverbal measures from both tests were designed to minimize need for visuomotor and processing speed and motor coordination, which may have accounted for differences when the RIAS was compared to the WAIS-III in samples with LDs and ADHD (Smith et al, 2009;Umphress, 2008). Edwards and Paulin suggest that the generalizability of their results was limited by a relatively small sample size, and the same can be said for our findings in that they were based on groups containing 34 subjects each.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…However, the current findings do make intuitive sense from the standpoint that both the WISC-IV and the RIAS were normed on large nationally stratified samples, their indexes and IQs are standardized and age corrected, and their verbal (VIX/VCI) and nonverbal (NIX/PRI) indexes assess conceptually similar constructs. Furthermore, the nonverbal measures from both tests were designed to minimize need for visuomotor and processing speed and motor coordination, which may have accounted for differences when the RIAS was compared to the WAIS-III in samples with LDs and ADHD (Smith et al, 2009;Umphress, 2008). Edwards and Paulin suggest that the generalizability of their results was limited by a relatively small sample size, and the same can be said for our findings in that they were based on groups containing 34 subjects each.…”
Section: Discussionmentioning
confidence: 55%
“…For all of these comparisons, covarying out the effects of time between injury and evaluation did not appreciably alter the results. Also, prior studies reported high correlations between RIAS and Wechsler indexes and IQs (Edwards & Paulin, 2007;Reynolds & Kamphaus, 2003;Smith et al, 2009;Umphress, 2008), further supporting the comparability of the IQ and index scores produced by these tests.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…RIAS were selected for their short administration time (30-40 min) and the possibility of applying the same test to all participants, since RIAS are normed in the ages from 3 to 94 years. RIAS constitute a valid test of intelligence and memory with adequate correlation with Wechsler's Intelligence Scale for Children and Wechsler's Adult Intelligence Scale (27,28).…”
Section: At Follow-upmentioning
confidence: 99%